Practical Implementation of the Right to be Forgotten in the Context of Google Spain Decision - Daniel Krošlák (Communication Today, 2025)
The concept of the right to be forgotten has arisen from desires of individuals to live their lives without being digitally stigmatized as a consequence of a particular action performed in the past. The right to be forgotten has been recently put into practice in the European Union by the decision of the Court of Justice of the European Union in Google Spain v. AEPD and Mario Costeja González. It holds that an internet search engine operator is responsible for the processing that it carries out regarding personal information which appears on web pages published by third parties. In this respect, it sets a milestone for EU data protection regarding search engines and, more generally, in the online world. The CJ EU grants the possibility for data subjects to request search engines, under certain conditions, to de-list links appearing in the search results based on a person’s name. In this article we take a closer look at the content of the aforementioned decision of the CJ EU and provide also information as to how it is practically implemented by following the steps that have been made by European data regulation authorities and the search engines Google, Bing and Yahoo. We conclude that Google and Bing managed to implement the decision in practice by creating a webpage containing a form which an affected person can use to request the removal of a search result that is among the data protected by the directive on the protection of individuals with regard to the processing of personal data and on the free movement of such data as interpreted by the CJ EU in the given decision.